Utilization of Tamarind (Tamarindus indica) Seed for Coagulation of Tofu Industry Wastewater (Study on Tamarind Seed Powder Concentration and Stirring Time) - Nurika, Irnia; Mulyarto, Aunur Rofiq; Afshari, Kunty (Fakultas Teknologi Pertanian Universitas Brawijaya, 2007)
The aim of this research was to evaluate the effectiveness of tamarind seed as a natural coagulant and stirring time in the quality improvement of waste water produced by tofu industries. The levels of tamarind seed flour added were 6 g/L, 10g/L and 14g/L, and the stirring time of 3 min and 5 min respectively. The experiment was carried out in triplicates and assessing the parameters of total soluble solids (TSS), BOD, dissolved oxygen (DO) and the pH.The results showed that the tamarind seed flour was able to reduce the level of parameters studied. The best treatment was obtained from the application of tamarind seed flour at a level of 14 g/L and 3 minutes stirring time. This combination was able to reduce Â 67.29% of the TSS level (from 425 mg/L to 139 mg/L) and 24.18% of the BOD5 value (from 71 mg/L to 53.83 mg/L) and to increase 53.85% of the DO value (from 1.8 mg/L to 3.90 mg/L) and pH value from 3.93 to 4.57. The BOD5 level of the treated water met the requirement of the quality standard of waste water for the tofu industry, except the TSS, DO and pH values.Keywords: coagulation, natural coagulant, tamarind seed